Hubungan Sleep Hygiene dengan Kualitas Tidur pada Mahasiswa Preklinik Semester 7 Fakultas Kedokteran Universitas Palangka Raya - Yemima Hasianna; Astri Widiarti; Agnes Immanuela Toemon (Direktorat Politeknik Kesehatan Makassar, 2025)
Sleep problems are common among students, especially medical students, due to high academic workload and demanding course requirements. Lack of sleep can have negative effects on physical and mental health, as well as academic performance. Sleep hygiene, which includes practices and habits that support good sleep, can be a non-pharmacological solution to this problem. This study aims to investigate the correlation between sleep hygiene and sleep quality among preclinical seventh-semester medical students at the Faculty of Medicine, University of Palangka Raya. The study employed an analytical observational cross-sectional design with 63 students selected through purposive sampling. Sleep hygiene was assessed using the Sleep Hygiene Index (SHI), and sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). The results showed that 9.5% of students had good sleep hygiene, 46% had moderate sleep hygiene, and 44.4% had poor sleep hygiene. Most students (84.1%) reported poor sleep quality. Spearman's correlation analysis revealed a statistically significant moderate positive correlation between sleep hygiene and sleep quality (r = 0.401, p = 0.001). It was concluded that there is a moderate positive correlation between sleep hygiene and sleep quality among preclinical students in the 7th semester of the Faculty of Medicine at Palangka Raya University. Keywords: Sleep hygiene; sleep quality; preclinical medical students